Arsenic survey in Dried Sediments of Maharlu Saline Lake - Taghizadeh, Mohammad Mehdi (Journal of Geoscience, Engineering, Environment, and Technology, 2018)
Being on the steep slope of Shiraz city and getting the main drainages, Maharlu Lake is always home to extensive levels of urban pollution. Prolonged droughts and drying of surface sediments of the lake happen usually in warm seasons of the year, and with the continuation of the droughts particles spread out from the surface into the surroundings of the lake. Arsenic and its compound are well known for its toxicity and carcinogenicity. Industrial and farming waste in upstream of the lake are the main sources of arsenic and may disperse in Maharlu Lake.   In this study, by meshing the lake’s surface and by sampling 15 points 3 kilometers away there determined the Arsenic amount. Then, the toxicity indexes and Mueller index together with its risks were studied before zoning of the lake through GIS and verification. The results showed that the average concentration of arsenic was 3.5 mg/ kg of surface sediment. The concentration has gone in most parts of the lake below normal as shown by Mueller index so that its contamination and lower-than-usual toxicity is deemed anthropogenic. Interpolations by GPI, LPI, and IDW methods demonstrated the north part of the lake more concentrated, likely due to the north lake farming and being the entrance of River Soltanabad. The verification of data has recognized the IDW method as the most accurate as regards interpolation.   According to the importance of heavy metals in the dust, samples should be taken from winds coming from the lakeside as dust hotspot to control the metals concentration.